The velocity of home blood pressure reduction in response to low-dose eplerenone combined with other antihypertensive drugs determined by exponential decay function analysis. (April 2014) - Elnagar, Noha; Satoh, Michihiro; Hosaka, Miki; Asayama, Kei; Ishikura, Kazuki; Obara, Taku; Mano, Nariyasu; Ohkubo, Takayoshi; Imai, Yutaka
Abstract Background/objective: Eplerenone is a highly selective aldosterone blocker, which has the potential to lower blood pressure (BP) in patients with hypertension. The objective of this study was to assess the hypotensive effects of low-dose eplerenone (25 mg) using home BP measurements. We also assessed the time required to reach 95% of the maximum antihypertensive effect (stabilization time) by analyzing exponential decay functions using home BP measurements. Methods: We reviewed the medical records of 83 hypertensive patients who were taking eplerenone 25 mg (age, 68.6 ± 11.8 years; men, 36.1%) in addition to other antihypertensive agents. Home BPs were averaged in each patient for the last 5 days of each observation period. The morning versus evening effect (M/E ratio) and the evening versus morning effect (E/M ratio) were calculated to assess the duration of action of eplerenone. Results: The mean home systolic/diastolic BPs at baseline were 136.8 ± 8.8/77.2 ± 9.3 mmHg, respectively. After 8 weeks of treatment with eplerenone, home systolic/diastolic BP significantly decreased by −7.1 ± 10.1/−2.6 ± 5.0 mmHg (p < 0.0001). The time for stabilization of home systolic and diastolic BPs was 13.7 days (p = 0.006) and 16.5 days (p = 0.001), respectively. When eplerenone was administered in the morning, the M/E ratio was 1.1 ± 0.3. The corresponding E/M ratio for evening administration was 0.9 ± 0.6. Although no nocturia was observed, there was a slight but significant increase in serum potassium levels (p = 0.03). Conclusions: Our data suggest that the combination of eplerenone with other antihypertensive drugs may be a promising therapeutic strategy for the treatment of essential hypertension.